Academic Information System Technology Acceptance Study: Case Study Universitas Internasional Batam - . Deli (Universitas Medan Area, 2019)
This study was conducted to determine the influence of perceived Usefulness, ease of use (Perceived Ease of Use), security and Privacy of student admissions (Acceptance Of SISFO) at Universitas Batam International through an approach using the Model Techonology acceptance model (TAM) using the analyzed variables are Perceived usefulness (PU), Perceived ease Of Use (PEU), Security and Privacy (SP). Respondents in this study involve active students of the International University of Batam, sampling conducted with purvosive sampling technique, related to the level of testing data obtained will be conducted by testing validity, realiability test, regression test against variable Perceived usefulness (PU), Perceived ease Of Use (PEU), Security and Privacy (SP). Data processing in the study will be conducted empirically using SPSS software, which results the above expected fromindependent variables is a significant test sample to determine the predicted acceptance rate to Academic information systems. The results of study show that testing of independent variable is significant and jointly has a positive influence on the dependent variable, there is the greatest influence on the Security and Privacy (SP) variable so the level of acceptance of academic information system is expected to provide security and maintain the confidentiality of user data.